The Effect Of Leaf Cutting (P Running) On Vegetative Growth Of Red Chillies (Capsicum Annum L.) - Ade Bayu Syahputra; Yusmaidar Sepriani; Khairul Rizal; Ika Ayu Putri Septiani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This research was carried out in Afd II Village, West Bilah District, Labuhan Batu Regency, starting in October 2021. The aim of the study was to determine the effect on the growth of Red Chili (Capsium Annum L) plants on cutting shoots on chili leaves. Chili is a staple for consumption in everyday life. Chili peppers can be made more productive by using the right gardening techniques. Maintenance measures such as cutting shoots of chili plants with a dichotomous are one approach to increase chili yields. Pruning dichotomous shoots seeks to remove less productive plant parts to maximize. This study used a completely randomized design (CRD) with 4 treatments with 5 replications, in order to obtain 22 experimental units, each bed planted with 30 chili plants. The total number of plants is 30 x 5 = 150 plants. For the experimental unit, 3 were selected to be used as plant samples. From the observations, if the F test shows a significant effect, it will be continued with the Duncan' New Multiple Range test (DNMRT) at a 5% significance level. As treatment, namely: A = Pruning 7 DAP, B = Pruning 4th branch, C = No pruning, D = Pruning 14 DAP. Cutting the tops of leaves to increase the yield of the red chili, the results of the study concluded: 1. Red chili plants that were trimmed branches made the chili plants taller, 2. Trimming leaves caused the emergence of new leaf blades to increase 3. And cutting leaf shoots was useful for improve the yield of chili plant quality. Based on the results of the study, it is recommended to trim the 4th branch because it can increase growth.